An assignment problem for n machines and m operators (2010)
The assignment problem is a special type of linear programming problem which is concerned with allocating in operators (men) to n machines (tasks) given that each operator is qualified for certain of the tasks. The output from each task is given as a function of the number of qualified men assigned to it. The assignment model is to be solved by conventional linear programming approach or transportation model approach. It is a square matrix, having equal number of rows and columns. It enables the assignment of men to task and the objective is to assign one man from row to one task from column so as to maximize total output and minimize the total cost.